The Influence of Digital Marketing, Brand Awareness, and Product Quality on Purchase Decisions for Somethinc Skincare Products - Galuh Malakiano; Ihwan Susila (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of digital marketing, brand awareness, and product quality on purchasing decisions for Somethinc skincare products. The research participants consisted of Somethinc product users in Surakarta, with a sample size of 179 respondents. A quantitative approach was employed, and data were collected through an online survey using Google Forms. The sample size was determined based on a power analysis to ensure statistical adequacy for capturing a diverse range of opinions and behaviors. Efforts were made to mitigate potential bias introduced by the online survey method, such as ensuring a demographic variety among respondents to reflect different consumer segments. Data analysis was conducted using SmartPLS 3.0 software, with hypothesis testing performed using the Partial Least Squares (PLS) method in two stages: evaluating the outer model and assessing the inner model. The online survey was carefully designed with questions to capture detailed insights into the respondents' perceptions of digital marketing, brand awareness, and product quality. Sample questions included [insert examples], which were specifically crafted to explore these factors comprehensively. The results indicate that digital marketing, brand awareness, and product quality have a positive and significant impact on purchasing decisions for Somethinc skincare products.